BIMBINGAN KONSELING INDIVIDUAL UNTUK MEMBANGUN KOMUNIKASI INTERPERSONAL POSITIF MELALUI TIM PSIKOLOG UNIVERSITAS AHMAD DAHLAN YOGYAKARTA - Anna Febrianty Setianingtyas; Ummu Hany Almasitoh; Titik Purwanti (SURAKARTA ABDIMAS JOURNAL, 2023)
Abstract Interpersonal communication can be called interpersonal communication. Interpersonal effectiveness is determined by how the message is conveyed. Positive attitude refers to at least two aspects of interpersonal communication. First, interpersonal communication is fostered if people have a positive attitude towards themselves. Second, positive feelings for the communication situation are essential for effective interaction. Communication quality is establishing and maintaining good interpersonal relationships through communication. Communication is effective when the sender receives and understands the message as intended, followed up with voluntary action by the recipient. It can improve the quality of interpersonal relationships, and there are no obstacles to it. This service is carried out to help several UAD's fair participants (counselees) get an overview of how the communication process effectively achieves its goals. This activity is carried out through individual counseling guidance methods with a team of psychologists at Ahmad Dahlan University Yogyakarta, with an evaluation of filling out a checklist sheet after counseling. Keywords : individual counseling, positive interpersonal communication